PUBLICATIONS OF THE WEEK. (Bookseller, 2004)
This article presents information on several books related to various issues. The list includes "Increasing Productivity of Intensive Rice Systems Through Site-Specific Nutrient Management," by Achim Dobermann, "Natural Enemies: An Introduction to Biological Control," by Ann Hajek, "The Speciation of Modern Homo Sapiens," by T.J. Crow and "Neanderthals and Modern Humans. An Ecological and Evolutionary Perspective," by Clive Finlayson.